PENGARUH PELATIHAN KERJA, JAMINAN SOSIAL DAN INSENTIF TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI PT. FUMIRA SEMARANG - Vendy Aries Martcahyo; Wahyu Hidayat; Sri Suryoko (Universitas Diponegoro, 2012)
Globalization creates fierce competition in the business world. In order to survive, a company needs to have a good performance to create effectiveness and efficiency. Employee performance to be one of the most important factors in achieving this. Job training, social security and incentives have been found to increase employee performance. PT. FUMIRA Semarang is a company engaged in the production of galvanized steel (zinc), which fluctuated in the achievement of annual targets. This study used an explanatory research approach to the 47 respondents. Sampling was done by using census. Data collection techniques in this study using interview techniques, questionnaires and literature study. The data obtained were analyzed qualitatively and quantitatively using analytical tools such as test validity, reliability testing, simple linear regression, multiple linear regression and hypothesis testing with the t test and F test. The results of statistical analysis known simple linear regression equation between job training with employee performance is Y = 11.517 + 0.396 X1. While the social security with employee performance equation is Y = 8.884 + 0.289 X2. Then incentives with employee performance equation is Y = 12.984 + 0.630 X3. Taken together influence job training, social security and incentives on employee performance can be determined by using linear regression analysis. The results of the calculation is Y = 8.428 + 0.027 X1 + 0.218 X2 + 0.207 X3. The conclusion of this study is job training, social security and incentives, both individually and together have a positive and significant influence on the performance employees. Suggestions for improving the performance of employees is expected to increase the company's attention for job training, social security and incentives that are likely to improve the performance of employees.